Antibacterial Activity of Visible Light-Activated TiO2 Thin Films with Low Level of Fe Doping. (25th November 2019) - Meng, Dan; Liu, Xiuhua; Xie, Yun; Du, Yang; Yang, Yong; Xiao, Chao
Abstract : Development of effective antibacterial visible light-activated photocatalytic materials in industries including wastewater treatment and food industry has attracted increasing attention. In this work, Fe-doped TiO2 thin films with different doping levels on a glass substrate were prepared by the sol-gel dip-coating method. The as-prepared films were characterized by Raman spectroscopy, X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and atomic force microscope (AFM). Raman spectroscopy and XRD results show the crystalline phase of titanium dioxide was anatase, and the range of the crystal size for the films was 19.24–22.24 nm. XPS results indicate that iron was in the form of Fe 3+ in Fe-doped TiO2 films. Regarding the antibacterial properties of TiO2 films, the order of antibacterial activity of TiO2 films was 0.1 at% Fe > 0.5 at% Fe > 1.0 at% TiO2 > bare TiO2 > 2.0 at% Fe > 3.45 at% Fe. 0.1 at% of Fe is the optimum dopant ratio related to antibacterial activity. 0.1 at% Fe-doped TiO2 film is highly efficient in inactivating E. coli under 3 h of visible light irradiation, and it remains efficient even in real dye waste water.